Потреба філософського осмислення нової освітньої парадигми - Пономарьов, Олександр Семенович (Міськдрук, 2016)
Overcoming the education crisis requires the formation of a new paradigm. Its development is possible only on the basis of the philosophical understanding of the nature and new tasks of the education. They are the consistency, focus on understanding, integrity of the educational process and the spiritual development of the individual.
Need of philosophical reflectionof the new educational paradigm
Keywords: філософія освіти; криза освіти; життєві цінності; педагогічні дослідження; інноваційні педагогічні технології; самовдосконалення